Когда стихи улыбаются - Асадов Эдуард Аркадьевич (Золотая серия поэзии, 2017)
Экземпляры: ф2 (20180601) / Инвентарный номер: / Цена: 260.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 90 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5